Essential Non-Technical Skills for Software Engineering and Engineering Sciences Graduates: A Case Study from North Cyprus - Farinola, Lawrence; Farinola, Toochi (Journal of Technical Education and Training, 2025)
This study examines key non-technical (soft) skills that impact the employability of software engineering and engineering sciences graduates in North Cyprus. A total of 50 stakeholders—comprising university lecturers, industry experts, postgraduate students, recent graduates, and job seekers—participated in a structured survey featuring 57 items across nine skill categories. Quantitative analysis using descriptive statistics (means, frequencies, standard deviations) revealed that skills such as written communication, leadership, patience, contextual problem-solving, brainstorming, professionalism, responsibility, planning, and empathy received mean scores above 3.5 on a 5-point scale, demonstrating strong perceived importance in recruitment processes. Findings underscore a notable gap in current engineering curricula regarding non-technical skills training. To address this, we advocate for the systematic integration of soft-skills development into university programs and recommend enhanced partnerships between academia and industry to improve workforce readiness.